A Comparative Investigation Of Workplace Approaches To Enhance Employee Satisfaction And Well-Being Between Indian It Industry & Foreign It Industry In India (Journal of Namibian Studies : History Politics Culture, 2023)
The growing significance of sustainability is shown by a comparison of workplace strategies used in the Indian and foreign IT industries in India with the goal of improving employee happiness and well-being. An organization's dedication, engagement, and retention of employees are greatly impacted by the work environment. Employee commitment and enthusiasm for their work have been linked to better organizational performance, according to research. Because it has a favorable effect on accomplishing corporate goals, employee retention has attracted a lot of interest from scholars and human resource experts. The purpose of this study is to look into how workplace policies in both domestic and international IT firms impact employee retention. A supportive work environment is strongly associated with employee retention, which in turn affects employees' decisions to stay with their companies, according to the literature currently in publication. The results highlight how important it is for managers to create a productive work environment that draws and keeps talent.242 workers in the Indian IT industry were given a survey to complete in order to collect data, and 198 of them correctly answered the questions. Individual-level evaluations and a comparison of the procedures of Indian and international IT organizations were part of the analysis. To increase employee retention and happiness in these companies, the research suggests establishing a lively and friendly workplace.